A study on non-muslim consumers' purchase intention of halal food in Korea - Tulsi Paudel; Wen Ya Li; Yeong Gug Kim; Yunho Ji (Global Business & Finance Review (GBFR), 2024)
Purpose: The demand for halal foods among non-Muslim customers is increasing in non-Muslim countries. This study investigates South Korean non-Muslim customers' halal food purchase intentions using an extended model of goal-directed behavior (EMGB). Design/methodology/approach: The study model combines halal awareness with the existing model of goal-directed behavior (MGB) variables and examines the moderating effect of word of mouth (WOM). Findings: The results indicated that attitudes, positive anticipated emotions, perceived behavioral control, and halal awareness influenced non-Muslim consumers' desire to purchase halal foods. Desire and halal awareness also pre- dicted purchase intentions. Moreover, word of mouth (WOM) had a significant moderating effect on the desire to purchase intentions of halal foods. Research limitations/implications: The results of this study can be utilized in managing the halal food business by providing information on non-Muslim consumer characteristics. Originality/value: This study aims to provide implications for the globalization of halal food by identifying specific variables that affect the halal food consumption behavior of non-Muslim consumers.
Keywords: 650; Halal food; Non-Muslim consumer; Model of goal-directed behavior; Purchase intention; Word of mouth; South Korea